Jensen Alpha and Market Climate - Breloer, Bernhard; Hühn, Hannah Lea; Scholz, Hendrik (Journal of Asset Management, 2016)
This article studies the impact of market climate on the classic Jensen alpha (JA) of equity funds. We show analytically that the one-factor JA of a fund consists of (i) the fund’s alpha based on the assumed multi-factor model driving fund returns and (ii) further components that are subject to time-dependent market phases of factor realizations. In our empirical study, we analyze JAs and respective fund rankings for a survivorship bias-free data set of 3102 US equity mutual funds. Our results show that factor realizations during the specific lifetime of a fund clearly affect its JA and rank position. This impact of factor realizations is particularly strong for funds with shorter lifetimes. To quantify the market climate impact, we compare classic JAs of funds with their time period-adjusted JAs, removing the influences of market phases. Finally, our main results are robust when applying alternative multi-factor models as return generating process of fund
Keywords: equity funds; Jensen alpha; fund ranking; market phases

Performance of International and Global Equity Mutual Funds: Do Country Momentum and Sector Momentum Matter? - Breloer, Bernhard; Scholz, Hendrik; Wilkens, Marco (Journal of Banking & Finance, 2014)
This is the first paper analyzing the impact of index momentum factors on the performance of international and global equity funds. Extending an international, index-based version of the Fama and French (1993) three-factor model by adding the factors of country momentum and sector momentum, we find that more than 50% of funds exhibit significant exposure to at least one of these factors. Including both new factors in performance evaluation clearly impacts results when analyzing (i) the risk-adjusted performance, (ii) the performance persistence of funds, and (iii) luck versus skill in the cross-section of funds. Our main results are robust against models which additionally cover a stock-based momentum factor as well as single country, regional and sector factors.
Keywords: International equity funds; Global equity funds; Country momentum; Sector momentum; Fund performance